MsDpo4—a DinB Homolog from Mycobacterium smegmatis—Is an Error-Prone DNA Polymerase That Can Promote G:T and T:G Mismatches - Sharma, Amit; Nair, Deepak T. (Journal of Nucleic Acids, 2012)
Error-prone DNA synthesis in prokaryotes imparts plasticity to the genome to allow for evolution in unfavorable environmental conditions, and this phenomenon is termed adaptive mutagenesis. At a molecular level, adaptive mutagenesis is mediated by upregulating the expression of specialized error-prone DNA polymerases that generally belong to the Y-family, such as the polypeptide product of the dinB gene in case of E. coli. However, unlike E. coli, it has been seen that expression of the homologs of dinB in Mycobacterium tuberculosis are not upregulated under conditions of stress. These studies suggest that DinB homologs in Mycobacteria might not be able to promote mismatches and participate in adaptive mutagenesis. We show that a representative homolog from Mycobacterium smegmatis (MsDpo4) can carry out template-dependent nucleotide incorporation and therefore is a DNA polymerase. In addition, it is seen that MsDpo4 is also capable of misincorporation with a significant ability to promote G:T and T:G mismatches. The frequency of misincorporation for these two mismatches is similar to that exhibited by archaeal and prokaryotic homologs. Overall, our data show that MsDpo4 has the capacity to facilitate transition mutations and can potentially impart plasticity to the genome.